The genome structure of the 1-FEH genes in wheat (Triticum aestivum L.): New markers to track stem carbohydrates and grain filling QTLs in breeding - Zhang, J.; Huang, S.; Fosu-Nyarko, J.; Dell, B.; McNeil, M.; Waters, I.; Moolhuijzen, Paula; Conocono, E.; Appels, R. (Springer, 2008)
Terminal drought tolerance of wheat is a major target in many areas in the world and is a particular focus in Western Australia. It is widely considered to relate to water soluble carbohydrate (WSC) levels such as fructan in the stem, as the head is maturing. Fructan exohydrolases are key enzymes during both fructan biosynthesis and mobilization. The wheat genome sequences of three fructan 1-exohydrolase (1-FEH) genes with seven exons and six introns were isolated by using the available 1-FEH w2 cDNA sequence. The major size differences among the three genes were located in intron 1 and intron 4. The three 1-FEH genes were mapped to Chinese Spring chromosome 6A, 6B and 6D based on polymerase chain reaction (PCR) polymorphisms and Southern hybridization. 1-FEH-6A, -6B and -6D corresponded to published cDNA sequences 1-FEH w1, w3 and w2, respectively. The overall correlation of the mRNA accumulation profile for the 1-FEH genes in stem and sheath leaf tissue in relation to the profile of soluble carbohydrate accumulation was consistent with their postulated role in stem soluble carbohydrate accumulation. The accumulation of the 1-FEH-6B (1-FEH w3) mRNA was 300 fold greater than that of 1-FEH-6A and -6D. The mRNA accumulation continued after the stem water soluble carbohydrate concentrations reached a peak, consistent with a role of 1-FEH-6B in the breakdown of soluble carbohydrate. The relationship between the 1-FEH genes and soluble carbohydrate accumulation is discussed and the 1-FEH-6B gene in particular is suggested to provide a new class of molecular marker for this trait. © 2008 Springer Science+Business Media B.V.